1994
DOI: 10.1083/jcb.125.6.1201
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic properties of nuclear lamins: lamin B is associated with sites of DNA replication.

Abstract: Abstract. The nuclear lamins form a fibrous structure, the nuclear lamina, at the periphery of the nucleus. Recent results suggest that lamins are also present as foci or spots in the nucleoplasm at various times during interphase of the cell cycle (Goldman, A. E., R. D. Moir, M. Montag-Lowy, M. Stewart, and R. D. Goldman. 1992. J. Cell Biol. 104:725-732; Bridger, J. M., I. R. Kill, M. O'Farrell, and C. J. Hutchison. 1993. J. Cell Sci. 104:297-306). In this report we demonstrate that during mid-late S-phase, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
202
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(229 citation statements)
references
References 57 publications
26
202
0
Order By: Relevance
“…The recent discovery that B-type lamins redistribute from the nuclear envelope to replication factories, in S-phase fibroblasts [23] has served to emphasise this role. It seems likely that a re-distribution of B-type lamins from the nuclear envelope to replication factories would require Lamin B was immunoisolated from quiescent and S-phase cultures of HDF which had been incubated in the presence of 32P i for 4 h, and separated by SDS-PAGE through 8% gels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent discovery that B-type lamins redistribute from the nuclear envelope to replication factories, in S-phase fibroblasts [23] has served to emphasise this role. It seems likely that a re-distribution of B-type lamins from the nuclear envelope to replication factories would require Lamin B was immunoisolated from quiescent and S-phase cultures of HDF which had been incubated in the presence of 32P i for 4 h, and separated by SDS-PAGE through 8% gels.…”
Section: Discussionmentioning
confidence: 99%
“…Thus most sites of DNA replication are not in contact with the lamina. However, recent studies have shown that, during S-phase, B-type lamins re-distribute from the nuclear envelope to active sites of DNA replication [23] indicating a direct role for lamins in DNA synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Internal type-A lamins have been reported in HeLa cells (Hozak et al, 1995) and in mammalian cells expressing lamin A-GFP fusion proteins (Broers et al, 1999). Type-A and type-B lamins are also seen as intranuclear foci in mammalian cultured cells (Bridger et al, 1993;Moir et al, 1994). These foci are thought to be intermediate stages of lamin processing, before their incorporation into the peripheral lamina (Goldman et al, 1992).…”
mentioning
confidence: 99%
“…The B-type lamins are expressed in all mammalian cells and have been highly conserved during vertebrate evolution. The B-type lamins have been reported to participate in many functions within the cell nucleus, including DNA replication (21) and the formation of the mitotic spindle (22). Recently, both lamin B1 and lamin B2 have been shown to be important for neuronal migration within the developing brain (23)(24)(25)(26).…”
mentioning
confidence: 99%